Bidirectional effects of neutrophils on Streptococcus oralis biofilms in vitro - Basmah M. Almaarik; Rizwan Ali; Paul R. Cooper; Michael R. Milward; Josefine Hirschfeld (Journal of Oral Microbiology)
Background Streptococcus oralis is a commensal bacterium and an early biofilm coloniser found in the human oral cavity. One of the biofilm matrix constituents is bacterial extracellular DNA (eDNA). Neutrophils are innate immune cells that respond to biofilms, employing antimicrobial mechanisms such as neutrophil extracellular trap (NET) and reactive oxygen species (ROS) release. Here, bidirectional effects of neutrophils on S. oralis biofilms were investigated.Materials and methods Isolated neutrophils were introduced to S. oralis biofilms at different stages of biofilm development. Biofilm quantity was assessed by crystal violet technique, confocal microscopy and CFU enumeration. Surface adhesion during shear stress was quantified by spectrophotometry. Bacterial and neutrophil extracellular DNA within biofilms and ROS production were analysed using fluorescence and luminescence assays, and neutrophil-eDNA interactions were investigated by flow cytometry and fluorescence microscopy.Results Neutrophils decreased S. oralis biofilm quantity transiently and reduced eDNA but did not affect biofilm surface adhesion. Unexpectedly, CFUs were increased by neutrophils. Bacterial DNA was found to co-localise with neutrophil membranes. Neutrophils produced elevated total and intracellular ROS, however, no NETs in response to biofilms.Conclusion Neutrophils in vitro are not excessively activated by S. oralis biofilms but are able to reduce biofilm quantity in the short-term, possibly through interfering with eDNA.